2018
DOI: 10.5511/plantbiotechnology.18.0515a
|View full text |Cite
|
Sign up to set email alerts
|

Long-term monitoring of bioluminescence circadian rhythms of cells in a transgenic <i>Arabidopsis</i> mesophyll protoplast culture

Abstract: The circadian system of plants is based on the cell-autonomously oscillating circadian clock. In the plant body, these cellular clocks are associated with each other, but their basic and intrinsic properties are still largely unknown. Here we report a method that enables long-term monitoring of bioluminescence circadian rhythms of a protoplast culture in a complete synthetic medium. From the leaves of Arabidopsis transgenic plants carrying the luciferase gene under a clockgene promoter, mesophyll protoplasts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Protoplasts would be suitable for investigations of cell-autonomous gene function by using the transiently introduced CRISPR/Cas9 system. Recently, we succeeded in stably monitoring the long-term bioluminescence circadian rhythms of Arabidopsis protoplasts (Nakamura and Oyama 2018). By monitoring the bioluminescence rhythms of individual protoplasts for a long term, it would be possible to experimentally reevaluate the mutation induction efficiencies of protoplasts.…”
mentioning
confidence: 99%
“…Protoplasts would be suitable for investigations of cell-autonomous gene function by using the transiently introduced CRISPR/Cas9 system. Recently, we succeeded in stably monitoring the long-term bioluminescence circadian rhythms of Arabidopsis protoplasts (Nakamura and Oyama 2018). By monitoring the bioluminescence rhythms of individual protoplasts for a long term, it would be possible to experimentally reevaluate the mutation induction efficiencies of protoplasts.…”
mentioning
confidence: 99%
“…1d and 3c). Previous studies have shown that the circadian rhythm damped in a diluted culture of protoplasts derived from shoot apex and leaves 12,27 . We assumed that intercellular communication might play a role in the maintenance of coherent rhythms among cells.…”
Section: Resultsmentioning
confidence: 98%
“…As previously reported 2730 , we prepared protoplasts from the leaves and roots of an Arabidopsis CCA1::LUC transgenic plant. Protoplasts of leaves are mainly mesophyll cells 27 and those of roots are presumedly a heterogeneous population with different cell types 31,32 . Cells derived from the protoplasts of leaves and roots are hereafter referred to as leaf-derived cells and root-derived cells, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in protoplasts support the presence of an autonomous clock in each plant cell [128,129,130]. To what extent are these cell-autonomous clocks coupled?…”
Section: Multiple Tissue- and Organ-specific Clocksmentioning
confidence: 99%